Sustainability in food retail industry through reverse logistics - Vijayan, Gowri; Kamarulzaman, Nitty Hirawaty; Mohamed, Zainal Abidin; Abdullah, Amin Mahir (ExcelingTech Publishers, 2014)
The food retail sector is known for its supply chain dependency. The delicate nature of its products emphasizes smooth movement of forward supply chain. The size of this industry however results in clogging of its supply chain from backward movement of packaging and food materials. The management of these products required adaptation of the supply chain to returns and waste management. This resulted in development of reverse logistics process, which has been successfully accepted by industries across the globe. Studies on reverse logistics adoption across global industries and its complete immersion into global supply chains have been widely conducted. The situation of research on reverse logistics adoption in Malaysian food retail industry is however restricted. The limited number of studies conducted on recent developments in Malaysian food retail industry and reverse logistics indicate a major gap in sustainable logistics studies. Considering the importance given to green movement by the government of Malaysia, it is necessary to understand this sustainable logistics practices. This study aims to investigate the level of reverse logistics adoption by retailers in Malaysia. The results highlight present scenario of reverse logistics processes of return and waste management, determinants to reverse logistics adoption, benefits obtained by retailers from reverse logistics and barriers to adoption of reverse logistics. The indifference of consumers to greening of retail operations acts as a major inhibitor to adoption of reverse practices by retailers. This study could be used as a precursor for further detailed studies on this issue.